Management of Antithrombotic Therapy in Atrial Fibrillation Patients Presenting with Acute Coronary Syndrome and/or Undergoing Percutaneous Coronary Intervention/ Stenting - Lip, Gregory Y. H.; Huber, Kurt; Andreotti, Felicita; Arnesen, Harald; Airaksinen, K. Juhani; Cuisset, Thomas; Kirchhof, Paulus; Marín, Francisco (Thrombosis and Haemostasis, 2010)
There remains uncertainty over optimal antithrombotic management strategy for patients with atrial fibrillation (AF) presenting with an acute coronary syndrome and/or undergoing percutaneous coronary intervention/stenting. Clinicians need to balance the risk of stroke and thromboembolism against the risk of recurrent cardiac ischaemia and/ or stent thrombosis, and the risk of bleeding. This consensus document comprehensively reviews the published evidence and presents a consensus statement on a ‘best practice’ antithrombotic therapy guideline for the management of antithrombotic therapy in such AF patients.
Keywords: Arial fibrillation; antithrombotic therapy; acute coronary syndrome; percutaneous coronary intervention; stenting; warfarin